2012
DOI: 10.1155/2012/740353
|View full text |Cite
|
Sign up to set email alerts
|

PKCαand ERβAre Associated with Triple-Negative Breast Cancers in African American and Caucasian Patients

Abstract: Although the incidence of breast cancer in the United States is higher in Caucasian women compared with African American women, African-American patients have more aggressive disease as characterized by a higher percentage of triple-negative breast cancers (TNBCs), high-grade tumors, and a higher mortality rate. PKCα is a biomarker associated with endocrine resistance and poor prognosis and ERβ is emerging as a protective biomarker. Immunohistochemical analysis of ERβ and PKCα expression was performed on 198 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
4
21
0
Order By: Relevance
“…Although the literature is conflicting regarding the level of PKCα expression in breast cancers compared to the normal breast [32-36], variability in PKCα expression amongst breast cancers and the link to endocrine resistance and tumor aggressiveness is clear. Based on three reports in the literature, the prevalence of PKCα expression in all breast cancers ranges between 28% to as high as 70% [3,4,37]. Even if the lowest estimate of 28% prevalence is the most accurate, this still represents a significant number of patients that may benefit from E2 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature is conflicting regarding the level of PKCα expression in breast cancers compared to the normal breast [32-36], variability in PKCα expression amongst breast cancers and the link to endocrine resistance and tumor aggressiveness is clear. Based on three reports in the literature, the prevalence of PKCα expression in all breast cancers ranges between 28% to as high as 70% [3,4,37]. Even if the lowest estimate of 28% prevalence is the most accurate, this still represents a significant number of patients that may benefit from E2 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Gö6976, a pharmacological inhibitor of cPKCs [43], abrogates ErbB2-mediated up-regulation of urokinase-type plasminogen activator (uPA) and cell invasion [44]. Whereas PKCα expression is higher in triple-negative breast cancers than to other subtypes [45], we still need to underscore meaningful associations of this PKC with genetic alterations specific for each breast cancer subtype.…”
Section: Pkcα: Tumor Promoter or Tumor Suppressor?mentioning
confidence: 99%
“…Further, research has indicated that PKC may be a critical factor in breast cancer antiestrogen resistance. PKC and ER expression are inversely related [47] and PKC is positively correlated with triple-negative breast cancers, which show no expression of ERs, progesterone receptors, or ErbB2 [50,51]. Breast cancer cells with overexpression of PKC also show high resistance for TAM treatment and hormone (e.g., estrogen)-independent growth [52][53][54][55], but inhibition of PKC induces TAM sensitivity [53][54][55].…”
Section: Pkc Isozymes and Cancermentioning
confidence: 99%